A new method for examining the dynamic performance of coordinate measuring machines. (February 2019) - Wozniak, Adam; Krajewski, Grzegorz; Byszewski, Maciej
Highlights: New method for testing the dynamic performance of CMM is proposed. An angle artefact assembled with a force sensor for CMM examination is applied. A new method is used for identification and evaluation of dynamic errors sources. The validity of the method is confirmed using diagnostics vibration analyser. Abstract: The proposition in this paper is a new method for the examination of the dynamic performance of coordinate measuring machines (CMM). The principle of the method is presented, and the method is used for identification and evaluation of dynamic error sources. The novelty of the proposed method is the application of an angle artefact connected with a force sensor for examination of the characteristics of the pressure force on the surface measured during the scanning measurement. Analysis of the course of the changeability of this force is crucial for determining the basic frequency characteristics of the dynamic performance of coordinate measuring machines. The validity of the method is experimentally confirmed on a Zeiss ACCURA bridge coordinate measuring machine by comparing the results coming from the new method vs. Bruel & Kjaer machine diagnostics vibration analyser.